(untitled) (Comprehensive Journal of Science, 2025)
This study aimed to identify the potential for adopting digital transformation through blockchains to improve the quality of accounting information at the Libyan Postal Company. A descriptive-analytical approach was used, appropriate for the purposes of the study. The study population consisted of all employees of the Finance Department and its affiliated departments and units, as well as the Internal Audit Office and its affiliated employees at the Libyan Postal Company, totaling 29 employees. Due to the small population size, a questionnaire was distributed to all staff. Twenty-nine questionnaires were distributed using a random sampling method, and 27 were retained. The data obtained were analyzed using SPSS statistical software. The results showed the potential for adopting digital transformation through blockchains at the Libyan Postal Company, as well as its benefits and role in improving the quality of accounting information. In light of these results, the study made several recommendations, including the need for companies to embrace digital transformation through blockchain, which has become a modern requirement, and the resulting change in the work environment and the provision of the necessary infrastructure. A sufficient budget should be allocated for this purpose, and appropriate training programs should be established for company employees in this technology, which requires advanced technological skills as well as accounting knowledge.